Nano-Designed Enzyme–Functionalized Hierarchical Metal–Oxide Mesoporous Thin Films: En Route to Versatile Biofuel Cells - Bellino, Martin Gonzalo; Soler Illia, Galo Juan de Avila Arturo (Wiley VCH Verlag, 2014)
Fil: Bellino, Martin Gonzalo. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina